A FEW GLOBAL TRENDS AND POINTS OF COMMONALITY IN QUALITY ASSURANCE IN HIGHER EDUCATION - Ruby, Alan (My University, 2012)
In this brief paper author offers a public policy perspective on quality assurance in higher education. Author begins by arguing that there is a growing public interest in quality assurance and offers some reasons for this increased attention. He suggests that the forces and factors that have fostered this greater interest are common to many countries and that this commonality has led to a convergence of the fundamental principles underlying quality assurance in different jurisdictions. He concludes by suggesting how these principles might apply at higher education institutions in new nations and emerging systems of higher education in the region.
Keywords: public policy perspective; Quality Assurance; ASSURANCE IN HIGHER EDUCATION; Higher education